Ethnobotanic survey of the galactagogue plants used by Brong and Koulango, two indigenous peoples in Gontougo region/Côte d’Ivoire - Olubunmi Adenike Akinwunmi (International Journal of Phytomedicine, 2019)
This study aims to inventory plants and traditional medicinal recipes used by the population of Tanda (Gontougo region, Côte d’Ivoire) to boost milk production in women. Using a questionnaire, the methods consisted in carrying out a survey near the traditional medicine actors of 15 localities. Among 47 actors of traditional medicine aged from 34 to 80 years investigated, 70.21 percent. were women. These women had more knowledge on the galactagogue plants than the men (29.79 percent.of the actors). They were represented by matrons, specialists in lactation, healers and saleswomen of medicinal plants. Among about fifteen listed galactagogue plants, Euphorbia hirta (Euphorbiaceae) was the most used plant. Leaves represented the majority of the medicinal preparations (73.33 percent.). These preparations were in 66.67 percent. of the cases associated with various other biological or mineral ingredients (pepper, meat, vegetables, ash, kaolin…). The direct application of crushings on mammary glands (cutaneous way) by friction constituted the principal route of administration (66.67 percent. of the medical receipts). Traditional medicine actors of the town of Tanda are actively interested in the search of solutions to the lacteal secretion issues which occur in the breast-feeding mothers. They have about fifteen medicinal plants which enable them to stimulate the production of maternal milk when a need is expressed.